Studi Kasus : Kejadian Penyakit Pada Farm Ayam Broiler Di Wilayah Kabupaten Cianjur - Suriansyah, Suriansyah; Ris, Adryani; Citra Septaningsih, Andi (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Therefore, early identification and analysis of disease causes areessential, particularly through preliminary examinations such asantibody titer measurement and anatomical pathology observation. Inaddition, laboratory testing for parasites, viruses, and bacteria playsa crucial role in establishing an accurate diagnosis and supportingeffective treatment decisions. The case animal in this report is a whitebroiler chicken exhibiting clinical signs of illness. The chicken wassourced from a poultry farm located in Cianjur Regency and hadshown symptoms of disease for four consecutive days. Clinical signsobserved included lethargy, reduced appetite, weight loss, dullplumage, swelling, and occasional abnormal respiratory sounds(gurgling or